Optimization of Design and Planing VHS Building Using Chronolux - Beta Paramita; Ismahnida Kamilia; Muhammad Iqbal Nurhidayat; Resty Ocktaviyane (Universitas Pendidikan Indonesia, 2016)
Gedebage integrated vocational high school (SMK) is a school which accommodates the concept of technopolis. The school has four programs: building engineering, family welfare education (PKK/food service), mechanical engineering, and tourism - which produce skilled and ready-to-work graduates. This article aims to recommend the sun exposure toward the building of the school, which is related to site planning and design strategies based on the duration of solar radiation on vegetation, and building facades as well as the distance between buildings through the use of Chronolux plug-in on Sketch-up Software. From the measurement, it is found that vegetation can reduce sky view factors (SVF) from 76.4 to 38.87%. For the building façade, it is able to reduce sun exposure from 4 hours 51 minutes to 3 hours 19 minutes with SVF from 47.26 to 38.11%. Meanwhile, the building distance of 9 m receives sun exposure from 9:00 am to 3.42 pm.